The Threat of the Deep State in the Nepali Context - Timalsina, Saroj Kumar; Shrestha, Suman Kumar (ILAM इलम, 2026)
This study examines the evolution, structure, and persistence of Nepal’s deep state—a network of entrenched, unelected actors that continues to undermine democracy and governance. Rooted in the Shah monarchy’s legacy, the deep state institutionalized power through the military, bureaucracy, judiciary, and elite patronage networks. Despite the restoration of multiparty democracy in 1990 and the establishment of a federal republic in 2008, informal power networks have persisted, adapting to new political frameworks and shaping policymaking beyond public accountability. The Nepali deep state is distinctive for its decentralized, multi-nodal structure, maintained by domestic elites and reinforced by external actors, including India, China, and Western donors, who often favor stability over genuine democratization. Mechanisms such as military autonomy, bureaucratic politicization, judicial manipulation, corporate-political alliances, and information control enable covert actors to maintain informal sovereignty, marginalize dissent, and limit transparency. Historical and contemporary case studies—including the 2005 royal coup, the 2006 People’s Movement, the 2015 Constitution, and the 2025 Gen-Z uprising—illustrate the adaptability of these networks in responding to democratic pressures. The study highlights that governance in Nepal is heavily conditioned by elite capture, patronage networks, and geopolitical dependencies, which collectively obstruct meaningful reforms. Policy pathways to counter the deep state include civilian oversight of security institutions, judicial and bureaucratic reform, digital governance safeguards, youth engagement, and balanced foreign policy. By mapping these domestic and international networks and identifying structural vulnerabilities, the research contributes to understanding the persistence of informal authority in Nepal and offers insights to strengthen democratic accountability, inclusivity, and transparency.